ANALISIS FAKTOR SOSIAL EKONOMI DAN DEMOGRAFI PEKERJA ANAK DI EKS-KARESIDENAN SURAKARTA TAHUN 2000 - Sutomo, Sutomo (Universitas Muhammdaiyah Surakarta, 2000)
More child labors in Indonesia under the minimum age who work, that is 15 year-old will cause a new difficult problem not only for the child himself who works, but also for the countrys future. This article is the result of a research on the economy social aspect and the child labors demography in the area of ex-residency of Surakarta. The locations of research are Sukoharjo, Karanganyar, Boyolali, Sragen, and Kodya Surakarta. The research population are the whole child labors who work in the formal and informal sector by using the method of snowball sampling and accidental sampling in taking the samples. The analysis used is description and regression analysis. The aspect analyzed is the income and working hours. Then the result of the multiple linear regression analysis can be mentioned that there is an influence of work status to the child labors income. Those who work in the informal sector get higher income. The male child labors get higher income than that of the female child labors get. The child labors income who study at school is higher than that of who do not.